2015
DOI: 10.1103/physreva.92.011601
|View full text |Cite
|
Sign up to set email alerts
|

Thermal suppression of phase separation in condensate mixtures

Abstract: We examine the role of thermal fluctuations in binary condensate mixtures of dilute atomic gases. In particular, we use Hartree-Fock-Bogoliubov with Popov approximation to probe the impact of non-condensate atoms to the phenomenon of phase-separation in two-component Bose-Einstein condensates. We demonstrate that, in comparison to T = 0, there is a suppression in the phase-separation of the binary condensates at T = 0. This arises from the interaction of the condensate atoms with the thermal cloud. We also sho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 33 publications
(66 reference statements)
4
39
0
Order By: Relevance
“…Fragmentation of bosonic mixtures in arrays of potential wells constitutes an important factor in determining their mixing properties and plays a crucial role, together with the repulsion between the mixture's components, in triggering spatial phase separation. A large amount of recent theoretical studies have revealed a colorful phenomenology ranging from phase separation mechanism 15,16 , demixing of dipolar mixtures 17 , and quantum emulsions 18,19 to the critical properties of quasiparticles spectrum across the transition 20 , thermal suppression 21 and the role of entanglement 22 in phase separation, and cascades of quantum phase transitions of vector bosons 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Fragmentation of bosonic mixtures in arrays of potential wells constitutes an important factor in determining their mixing properties and plays a crucial role, together with the repulsion between the mixture's components, in triggering spatial phase separation. A large amount of recent theoretical studies have revealed a colorful phenomenology ranging from phase separation mechanism 15,16 , demixing of dipolar mixtures 17 , and quantum emulsions 18,19 to the critical properties of quasiparticles spectrum across the transition 20 , thermal suppression 21 and the role of entanglement 22 in phase separation, and cascades of quantum phase transitions of vector bosons 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Hard-sphere bosonic systems were considered within a self-consistent t-matrix theory in the HFB approximation [29] and beyond [30]. Recently, the HFB approximation was applied to study phase separation in two-component Bose-condensates [31]. This approximation was also used to describe a finiteparticle trapped one-dimensional Bose-system [32].…”
Section: Introductionmentioning
confidence: 99%
“…More sophisticated derivations take into account the presence of an external trap as well as corrections from the finite particles' number and the thickness of the overlapping region. Properties of the phase separation at finite temperatures can also be examined [98,99]. For our purposes, it is useful to have in mind that the physics of mixtures of a few bosons will show the footprints of the phase separation phenomena that would appear at the large atom limit.…”
Section: B Phase Separationmentioning
confidence: 99%